Aligned Carbon Nanotubes Physics, Concepts, Fabrication and Devices - Ren, Zhifeng; Lan, Yucheng; Wang, Yang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book gives a survey of the physics and fabrication of carbon nanotubes and their applications in optics, electronics, chemistry and biotechnology. It focuses on the structural characterization of various carbon nanotubes, fabrication of vertically or parallel aligned carbon nanotubes on substrates or in composites, physical properties for their alignment, and applications of aligned carbon nanotubes in field emission, optical antennas, light transmission, solar cells, chemical devices, bio-devices, and many others. Major fabrication methods are illustrated in detail, particularly the most widely used PECVD growth technique on which various device integration schemes are based, followed by applications such as electrical interconnects, nanodiodes, optical antennas, and nanocoax solar cells, whereas current limitations and challenges are also be discussed to lay the foundation for future developments.
Introduction to Carbon -- Introduction to Carbon Nanotubes -- Growth Techniques of Carbon Nanotubes -- Chemical Vapor Deposition of Carbon Nanotubes -- Physics of Direct Current Plasma-Enhanced Chemical Vapor Deposition -- Technologies to Achieve Carbon Nanotube Alignment -- Measurement Techniques of Aligned Carbon Nanotubes -- Properties and Applications of Aligned Carbon Nanotube Arrays -- Potential Applications of Carbon Nanotube Arrays.
Keywords: Physics; Engineering; Optical materials; Nanotechnology; Physics; Nanoscale Science and Technology; Nanotechnology; Nanotechnology and Microengineering; Optical and Electronic Materials; Semiconductors